STUDI PEMBUATAN SERBUK EFFERVESCENT TEMULAWAK (Curcuma xanthorrhiza Roxb) KAJIAN SUHU PENGERING, KONSENTRASI DEKSTRIN, KONSENTRASI ASAM SITRAT DAN Na-BIKARBONAT - Rakhmad Wiyono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2011)
This research aimed to get the combination of drying temperature and dextrin concentration against the quality of temulawak’s essence, and the combination between citric acid and Na- Bicarbonate treatment against temulawak’s effervescent powder quality. The result of the first step shows that the treatment combination between 20% of dextrin concentration and 50°C of drying temperature which is the best treatment of the first step from temulawak’s powder essence that has characteristics on 10.11% of water content, ( L*) 55.10 of brightness level, (a*) 14.56 of redness level, ( b*) 44.20 of yellowness level, 24.63% of rendement, 5.63 of pH; 2.78 of water re-absorption; 1.88% of sugar content reduction; 62.27% antioxidant content, 5.55 obtains panellists’ assessment against color, 5.95 of taste, and 4.15 of aroma. The result of the second step shows that the treatment combination between 10% citric acid and 20% Na-bicarbonate that is the best treatment of the second step that has characteristics on 7.48% of water content, (L*) 59.37 of brightness level, (a*) 14.53 of redness level, (b*) 46.50 of yellowness level, 5.33 of pH, 88.17 of dissolving rate, 2.49% of sugar content reduction, and 46.53% of antioxidant content. The conclusion of this research is the best treatment combination on the first step is 20% of dextrin concentration and 50°C drying temperature, while at the second step is 10% citric acid concentration and 20% Na-bicarbonate. The advice of this research is its necessary to analyze the curcuminoid content as an active antioxidant compound in temulawak.